Create a Diversified Market and Build a Multi-vendor E-Commerce Platform - Babu, Samuel; Mehta, Suheli (Journal of Global Economy, Business and Finance, 2024)
In today's digital landscape, e-commerce websites serve as crucial hubs for online businesses, driving exponential growth in the realm of internet-based commerce. However, while the prevalence of e-commerce is undeniable, its reach in underdeveloped regions remains limited, leaving ample room for expansion and improvement. This paper delves into the multifaceted process of developing an e- commerce website, addressing key challenges and presenting optimal solutions. The development journey is segmented into two fundamental components: front-end and back-end development, each playing a pivotal role in delivering a seamless user experience. Furthermore, database design is explored in detail, emphasizing the importance of relational connectivity for robust functionality and efficient data management. Join us as we navigate through the intricacies of e-commerce development, striving to unlock its full potential on a global scale. "